Relationship disorders and cognitive functioning in young children - Akdemir, Devrim; Chadaroğlu-Cetin, Füsun; Ozusta, Seniz; Karadağ, Ferda (The Turkish Journal of Pediatrics, 2010)
The aim of this study was to investigate the cognitive functioning of young children with or without relationship disorders with their mother. Mother-infant dyads were recruited during the first three postpartum days. Parent Infant Relationship Global Assessment Scale (PIRGAS) scores and mother-child relationship disorders were decided when children were 41-49 months of age by integrating the data obtained from psychiatric interview with mothers, Clinical Problem Solving Procedure (CPSP) and home observation. Cognitive functioning of young children was evaluated with Stanford-Binet Intelligence Scale. The young children without relationship problems/disorders had higher intelligence quotient (IQ) scores even after controlling for the effect of independent variables on cognitive functioning. These findings suggest that there is a link between the quality of the mother-child relationship and cognitive functioning in young children. Therefore, physicians should assess the interactions of children with their mothers even if they are brought for reasons other than relationship problems.